Entrepreneurial intention as a predictor of anxiety in university students in northern Peru - Guevara Musayon, Oscar Eden (2025)
The purpose of this research was to establish the extent to which the variable of entrepreneurial intention can predict anxiety levels among a group of university students in northern Peru. A quantitative approach was chosen, following a post-positivist paradigm, with a non-experimental and cross-sectional design, establishing a correlational-causal level. The sample consisted of 240 participants. The entrepreneurial intention questionnaire by Rueda, Moriano, and Liñán (2015) and the Generalized Anxiety Scale GAD-7 by Spitzer et al. (2006) were used. The results show a significant negative correlation between entrepreneurial intention and anxiety (Rho = -0.421, p < 0.01). The logistic regression model indicates that entrepreneurial intention explains 5.5% of the variability in anxiety (Nagelkerke R² = 0.055, p < 0.01), with a predictive effect confirmed by the Chi-square test (24.69, p < 0.001). Additionally, 87.9% of students exhibit high entrepreneurial intention, while 68.3% report anxiety, primarily mild (36.7%). It is concluded that entrepreneurial intention can act as a protective mechanism against anxiety in uncertain environments. These findings highlight the importance of strengthening entrepreneurial training programs, aligned with SDG 3 (Good Health and Well-being) and SDG 4 (Quality Education), to improve mental health and youth employability.